Correlation of circulating betatrophin concentrations with insulin secretion capacity, evaluated by glucagon stimulation tests. Issue 5 (5th February 2015) - Tokumoto, S.; Hamamoto, Y.; Fujimoto, K.; Yamaguchi, E.; Okamura, E.; Honjo, S.; Ikeda, H.; Wada, Y.; Hamasaki, A.; Koshiyama, H.
Abstract: Aim: To investigate the relationship between plasma betatrophin concentrations and insulin secretion capacity in people with Type 2 diabetes. Methods: Glucagon stimulation tests (1 mg) were performed in 70 people with Type 2 diabetes after an overnight fast. Plasma betatrophin concentrations were measured using an enzyme‐linked immunosorbent assay. Insulin secretion capacity was evaluated by measuring increments of C‐peptide concentration in response to glucagon stimulation, and creatinine clearance was determined by comparing creatinine concentrations in serum and 24‐h urine samples. Results: Plasma betatrophin concentrations were positively correlated with duration of Type 2 diabetes ( r  =   0.34, P  =   0.003), and negatively correlated with increments of C‐peptide concentration ( r  =   0.37, P  =   0.001) and creatinine clearance ( r  =   0.37, P  =   0.001). The correlation with increments of C‐peptide concentration remained significant after adjustment for age and duration of Type 2 diabetes ( r  =   0.25, P  =   0.037). Multivariate analysis identified age and increments of C‐peptide concentration as independent factors associated with plasma betatrophin levels. Conclusion: Plasma betatrophin levels inversely correlate with insulin secretion capacity, suggesting that betatrophin levels are regulated by insulin secretion capacity in humans. What's new?: Betatrophin has recently been identified as a potential stimulator of β‐cell mass expansion in mice; however, the pathophysiological role of betatrophin in people with diabetes is still unknown. This is the first report to show that betatrophin concentrations correlate negatively with insulin secretion capacity and positively with duration of Type 2 diabetes.